2007
DOI: 10.1016/j.ijgo.2006.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two World Health Organization partographs

Abstract: The simplified WHO partograph was more user-friendly, was more to be completed than the composite partograph, and was associated with better labor outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 1 publication
7
76
0
4
Order By: Relevance
“…Labor crossing the action line was observed in 10.8% and 1.96% parturients in the composite and simplified group respectively (p=0.005). Almost similar observations were made by the study done at Vellore where labor had crossed the action line in 7.0% in the composite group as compared to 1.0% in the simplified group (12). Action line was crossed in 38% of cases in the composite partograph group at a study done in Liverpool (15).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Labor crossing the action line was observed in 10.8% and 1.96% parturients in the composite and simplified group respectively (p=0.005). Almost similar observations were made by the study done at Vellore where labor had crossed the action line in 7.0% in the composite group as compared to 1.0% in the simplified group (12). Action line was crossed in 38% of cases in the composite partograph group at a study done in Liverpool (15).…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, labor crossing the alert line was found in 28.2% of patients in the composite partograph group and 13.7% of patients in the simplified partograph group (p=0.0001). Similar study done at Vellore, India reports 17.7% and 15.1% in the two groups respectively (12). A study done in Pakistan showed 11.6% of labors to cross the alert line in the simplified partograph group (13).…”
Section: Discussionmentioning
confidence: 60%
“…In the classical Fisher partogram, cervical dilatation and action line are the recorded parameters of the progress of labor. It consists of two straight diagonal parallel lines, where the action line is parallel and at the right of the alert line, but the fetal head descent is not included (21). The alert line drawn from APGAR at 1 min 9 9 1.000 (mean±SD) APGAR at 5 min 10 10 1.000 (mean±SD) 3 cm to 10 cm represents the dilatation rate.…”
Section: Discussionmentioning
confidence: 99%
“…An early decision about the appropriate management to overcome the labor delay is possible with the use of the new type of partogram with only one graphic line (22). The wide variation in the published records of labor observation suggests that midwives and some obstetricians prioritized cervical dilatation over the other parameters (21). It is notable that the partogram and particularly the new partogram can only be used by health workers with adequate experience in midwifery and who are responsible and authorized to observe and conduct normal labor, perform vaginal examination, assess cervical dilatation and fetal head descent accurately, and immediately note cervical dilatation and head descent on a graph against time.…”
Section: Discussionmentioning
confidence: 99%
“…There were some other minor changes which include considering two squares in 1 hour instead of one square in 1 hour in cervical dilatation curve. 4 WHO further modified the partograph for the third time, this time for used by skilled attendants in health centre. This simplified partograph is colour coded.…”
Section: Introductionmentioning
confidence: 99%